Analisis Pengelolaan Keuangan Desa Pada Desa Bonto Jai Kecamatan Bissapu Kabupaten Bantaeng - Utami, Sri; Rayyani, Wa Ode; Sahrulllah, Sahrulllah (universitas teuku umar, 2025)
This study uses a qualitative approach to understand financial planning and management in Bonto Jai Village, Bissappu District, Bantaeng Regency. Data were collected through interviews, documentation, and observation, and analyzed inductively and comparatively. Informants included the Village Head, Village Secretary, and community representatives. The focus of the study was to describe phenomena related to village financial management and compare them with the Village Financial Management Guidelines according to Permendagri No. 20 of 2018. The results of the study showed that village financial management had followed the provisions and principles stipulated in Permendagri Number 20 of 2018. Bontojai Village has implemented stages of financial management which include planning involving community participation, implementation that takes place transparently and accountably, supervision from the Village Consultative Body (BPD), and accountability that is conveyed openly to the community. Keywords: Village financial management, Minister of Home Affairs Regulation Number 20 of 2018, Transparency, Accountability